Optimised hydrogen production by aqueous phase reforming of glycerol on Pt/Al2O3. (2nd November 2016) - Subramanian, Nachal D.; Callison, June; Catlow, C. Richard A.; Wells, Peter P.; Dimitratos, Nikolaos
Abstract: Aqueous phase reforming of glycerol was studied over a series of γ-Al2 O3 supported metal nanoparticle catalysts for hydrogen production in a batch reactor. Of the metals studied, Pt/Al2 O3 was found to be the most active catalyst under the conditions tested. A further systematic study on the impact of reaction parameters, including stirring speed, pressure, temperature, and substrate/metal molar ratio, was conducted and the optimum conditions for hydrogen production (and kinetic regime) were determined as 240 °C, 42 bar, 1000 rpm, and substrate/metal molar ratio ≥ 4100 for a 10 wt% glycerol feed. The glycerol conversion and hydrogen yield achieved at these conditions were 18% and 17%, respectively, with negligible CO and CH4 formation. Analysis of the spent catalyst using FTIR provides an indication that the reaction pathway includes glycerol dehydrogenation and dehydration steps in the liquid phase in addition to typical reforming and water gas shift reactions in the gas phase. Graphical abstract: A systematic study of the aqueous phase reforming of glycerol over Pt/Al2 O3 catalyst yielded the optimum conditions for a batch system and characterisation of the spent catalyst provided insights into possible reaction pathways. Highlights: A systematic study of glycerol APR over Pt/Al2 O3 in a batch reactor is presented. The catalytic performance is strongly influenced by reaction variables. The reaction pathway includes dehydrogenation and dehydration steps besides reforming.